Plasma-Immersion Formation of High-Intensity Ion Beams; Technical Physics Letters; Vol. 43, iss. 12 - Ryabchikov A. I. Aleksandr Ilyich; Ananin P. S. Petr Semenovich; Dektyarev S. V. Sergey Valentinovich; Sivin D. O. Denis Olegovich; Shevelev A. E. Aleksey Eduardovich (2017, 2017)
Title screen